The sociocultural and productivity nexus in yam farming in Nigeria - E.-O. S. Ema; J. E. Obidegwu; E. M. Akpabio (Пищевые системы)
Socio-cultural structures of yam production are largely shaped by the tradition, religion, beliefs, taboos, myths, spirituality and social relationships. Obudu community was the focus to examine the implications of these structures on yam productivity and sustainability. Data was collected through 60 interviews, 2 public meetings, 3 focus group discussions, local informants, review of literature, including secondary and grey literature and keen observation. Our findings reveal a range of indices of respondents’ perception as measures of productivity. The native and the ‘aged’ majority of the population were more conservative in their farming practice exhibiting deeper attachment to traditional practices and ecological wholesomeness with decreasing material productivity and performance in yield outputs, though not so significant. The socially mobile non-natives and the younger demographic groups were open to the modern farming approach targeting the quantity and tons of yam tubers and were not so keen on the overall health and integrity of the ecological system that makes sustainable production and human existence possible. The results emphasize the need to look beyond the improvement in material productivity as other non-material indices of productivity should be explored. More rigorous quantitative and long-term trend analysis should be conducted to assess the productivity performance trend associated with the natural ecological health and yam outputs for the study area.